Negative Prognostic Impact of Smoking on Long-term Survival in Patients With Nasopharyngeal Carcinoma Treated With Curative (Chemo)radiotherapy - Pala, Miloslav; Novakova, Pavla; Drbohlavova, Tereza; Vrana, Antonin; Pechacova, Zdenka; Votavova, Karolina; Subrt, Adam; Krejci, Daniel; Holeckova, Petra; Tesarova, Petra (In vivo (Athens, Greece), 2023)
BACKGROUND/AIM: To evaluate the effectiveness of curative (chemo)radiotherapy in patients with nasopharyngeal carcinoma and to identify prognostic factors influencing treatment outcomes. PATIENTS AND METHODS: We conducted a retrospective study of 73 consecutive patients, treated with definitive (chemo)radiotherapy from 2002 to 2019 (median stage III/IV 78%). The median total dose of radiotherapy achieved was 70 Gy. Concomitant chemotherapy was given to 82% of patients. RESULTS: The five- and ten-year locoregional controls were 73% and 72%, respectively; the five- and ten-year distant controls were 93% and 93%, respectively. The five- and ten-year overall survival rates were 46% and 34%, respectively. A multivariate analysis identified age, smoking, and the initial response to treatment as the strongest prognostic factors in predicting survival. CONCLUSION: Smoking ≤5 years before starting curative (chemo)radiotherapy for nasopharyngeal carcinoma was shown to be an independent negative prognostic factor for overall survival with a four-fold higher risk of death compared to non-smokers.
Keywords: výsledek terapie; retrospektivní studie; nasofaryngeální karcinom; prognóza; Neoplasm Staging; Nasopharyngeal Carcinoma; chemoradiotherapy; nádory nosohltanu; Smoking; prognostic factors; Treatment Outcome; lidé; smoking; Humans; Chemoradiotherapy; Nasopharyngeal Neoplasms; Prognosis; chemoradioterapie; Nasopharyngeal carcinoma; Retrospective Studies; curative radiotherapy; staging nádorů; kouření